Use of the intradermal leishmanin test (Montenegro skin test) for feline visceral leishmaniosis: Detection of cellular immunity - Alves, Maria Luana; Silva, Diogo Tiago da; Spada, Júlio Cesar Pereira; Leonel, João Augusto Franco; Benassi, Julia Cristina; Pereira, Nuno Wolfgang Balbini; Vioti, Geovanna; Alves-Martin, Maria Fernanda [UNESP]; Paula, Nathália Frigo de Almeida; Starke-Buzetti, Wilma Aparecida [UNESP]; Oliveira, Trícia Maria Ferreira de Sousa (My University, 2022)
This study evaluated the humoral and cellular response in 100 cats living in an endemic area of visceral leishmaniosis (VL) using the Montenegro Skin Test (MST) and serological diagnosis and compared the MST with other diagnostic techniques. Sixty 60%, (60/100) cats were positive for MST and the diameter of positive skin reactions ranged from 5 to 9 mm. By serological methods, 74% (74/100) and 34% (34/100) had antibodies against Leishmania spp. by Immunofluorescence Antibody Test (IFAT) and Indirect Enzyme-Linked Immunosorbent Assay (ELISA), respectively. Comparing tests, the observed profiles were (1) IFAT (+)/MST (−) = 27 cats, (2) IFAT(−)/MST(+) = 13 cats, (3) IFAT(+)/MST(+) = 47 cats, (4) ELISA(+)/MST(−) = 12 cats, (5) ELISA(−)/MST(+) = 38 cats and (6) ELISA(+)/MST(+) = 22 cats. Through the combination of serological diagnosis and MST, a positivity frequency of 87% (87/100) by IFAT + MST and 72% (72/100) by ELISA + MST was identified in this cat population. Five cats (5%) were positive for Leishmania donovani complex DNA by molecular analysis, and two cats (2%) had Leishmania spp. amastigotes in lymph node smears. Therefore, the agreement between tests was classified as poor for all tests by Kappa index. The IFAT (+)/MST (+) response was the most frequent considering all cats (47%; 47/100); nonetheless, the most frequent immune expression in Polymerase Chain Reaction (PCR)-positive cats was the IFAT (+)/MST (−) profile (80%; 4/5). Five sick and PCR-positive cats, negative for Feline Immunodeficiency Virus (FIV) and Feline Leukemia Virus (FeLV), that PCR sequencing matched 100% with L. donovani complex, all but one were MST negative. These results suggest that cats develop a significant cellular response against infection by parasites of the L. donovani complex, and most PCR and parasitological positive cats may be unable to develop a significant cellular response.
Keywords: Cellular response; Delayed-type hypersensitivity; Domestic cat; Serology